If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-8q + 2) = -2(-9 + -7q) Reorder the terms: -1(2 + -8q) = -2(-9 + -7q) (2 * -1 + -8q * -1) = -2(-9 + -7q) (-2 + 8q) = -2(-9 + -7q) -2 + 8q = (-9 * -2 + -7q * -2) -2 + 8q = (18 + 14q) Solving -2 + 8q = 18 + 14q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-14q' to each side of the equation. -2 + 8q + -14q = 18 + 14q + -14q Combine like terms: 8q + -14q = -6q -2 + -6q = 18 + 14q + -14q Combine like terms: 14q + -14q = 0 -2 + -6q = 18 + 0 -2 + -6q = 18 Add '2' to each side of the equation. -2 + 2 + -6q = 18 + 2 Combine like terms: -2 + 2 = 0 0 + -6q = 18 + 2 -6q = 18 + 2 Combine like terms: 18 + 2 = 20 -6q = 20 Divide each side by '-6'. q = -3.333333333 Simplifying q = -3.333333333
| 4x-32=-y | | 2(9q+3)=-2(2+3q)-2q | | 12x+2x=84 | | 24x^3+30x^2= | | -9=-(1+k)-4k | | 14x+x=90 | | 13+4x=9-6x | | X+2/3x+1/3x=180 | | -46=5x-1/3x | | 4X.3X-2=2X | | 100/b=-4 | | 2n+3.8=6.6 | | 4+x=-11+6x | | x-27=-5 | | 5(3c-1)-6=13c+7 | | 1+9x=-4+3x | | ln(x-1)+ln(x+2)=ln(45) | | 2t-4=3(t+2) | | 16(5+2)-8=16*5+24 | | A=937.4/100.8 | | -3n-(-2+n)=-6 | | 27-17=2(x-3) | | -15.54/2.1=z | | 36+3y-8=13y-14-3y | | 15x^2-81x-54=0 | | 12x-15/21= | | 2(n+4)-(-6n-8)=7n | | 3+6x=5+2x | | 4y=-2(-1)-8 | | -(-2x-18)=-62 | | -81-4/-37=z | | 2x-3=21+10 |